The thinking of the exceptional. Auschwitz, philosophy, history, and representation 75 years later - Fernández López, José Antonio (Revista de Filosofía, 2021)
The radical event symbolized by Auschwitz still demands a discursive articulation, and much follow-up thinking 75 years after the liberation of the camps. Does Auschwitz have that much relevance and universal significance? Are its implications so binding that such an event transcends the limits of its own radical particularity? To determine the meaning of an event such as the one symbolized by Auschwitz Lager has been and will remain a challenge to Philosophy with profound aesthetic, metaphysical and ethical-political implications.
Keywords: Auschwitz; holocaust; singularity; representation; limits